Changes in public order after the opening of a medically supervised safer injecting facility for illicit injection drug users - Wood, Evan (Canadian Medical Association, 2004)
BACKGROUND: North America's first medically supervised safer injecting facility for illicit injection drug users was opened in Vancouver on Sept. 22, 2003. Although similar facilities exist in a number of European cities and in Sydney, Australia, no standardized evaluations of their impact have been presented in the scientific literature. METHODS: Using a standardized prospective data collection protocol, we measured injection-related public order problems during the 6 weeks before and the 12 weeks after the opening of the safer injecting facility in Vancouver. We measured changes in the number of drug users injecting in public, publicly discarded syringes and injection-related litter. We used Poisson log-linear regression models to evaluate changes in these public order indicators while considering potential confounding variables such as police presence and rainfall. RESULTS: In stratified linear regression models, the 12-week period after the facility's opening was independently associated with reductions in the number of drug users injecting in public (p < 0.001), publicly discarded syringes (p < 0.001) and injection-related litter (p < 0.001). The predicted mean daily number of drug users injecting in public was 4.3 (95% confidence interval [CI] 3.5–5.4) during the period before the facility's opening and 2.4 (95% CI 1.9–3.0) after the opening; the corresponding predicted mean daily numbers of publicly discarded syringes were 11.5 (95% CI 10.0–13.2) and 5.4 (95% CI 4.7–6.2). Externally compiled statistics from the city of Vancouver on the number of syringes discarded in outdoor safe disposal boxes were consistent with our findings. INTERPRETATION: The opening of the safer injecting facility was independently associated with improvements in several measures of public order, including reduced public injection drug use and public syringe disposal.